Attention and P300-based BCI performance in people with amyotrophic lateral sclerosis - Riccio, Angela; Simione, Luca; Schettini, Francesca; Pizzimenti, Alessia; Inghilleri, Maurizio; Olivetti Belardinelli, Marta; Mattia, Donatella; Cincotti, Febo (Frontiers in Human Neuroscience, 2013)
The purpose of this study was to investigate the support of attentional and memory processes in controlling a P300-based brain-computer interface (BCI) in people suffering from amyotrophic lateral sclerosis (ALS). Eight people with ALS performed two behavioural tasks: i) a rapid serial visual presentation (RSVP) task, screening the temporal filtering capacity and the speed of the update of the attentive filter, and ii) a change detection task, screening the memory capacity and the spatial filtering capacity. The participants were also asked to perform a P300-based BCI spelling task. By using correlation and regression analyses, we found that only the temporal filtering capacity in the RSVP task was a predictor of both the P300-based BCI accuracy and of the amplitude of the P300 elicited performing the BCI task. We concluded that the ability to keep the attentional filter active during the selection of a target influences performance in BCI control.